Dimensi Teologi Pendidikan Islam Dalam Al Quran - Cucu Komariah; Adang Hambali; Andewi Suhartini (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
This research analyzes the theological dimensions of Islamic education in the Koran. The research method uses a qualitative type of literature survey (secondary). The data source in this research is to look for literary sources related to the theological dimensions of Islamic education in the Al-Quran in the form of literature studies of various reliable information related to existing problems such as books, magazines, and written materials discussing the substance of God. from all its aspects and its connection with nature. The research results show that theology always means discourse or talk about God. The educational dimensions of human nature and its unique potential are as follows. There are four dimensions: Individual Dimensions, Social Dimensions, Dimensions of Decency, and Religious Dimensions. Possible educational areas for improvement are complete development and incomplete development. The basis of Islamic education is the Koran. Hadith and Ijma.